Literasi Ekonomi Islam, Religiusitas, dan Intensi Transaksi E-Commerce: Peran Mediasi Sikap Konsumen Muslim - Auliya Auliya Elvansa Santoso; Kusnul Ciptanila Yuni K; Imam Sopingi; Peni Haryanti (Kartika: Jurnal Studi Keislaman, 2026)
Researching how Muslims make purchases online is becoming more important as e-commerce in Indonesia continues to expand. The purpose of this study is to analyze the influence of Islamic economic literacy and religious values on the intention to engage in e-commerce transactions, with Muslim consumer attitudes serving as a mediating variable, among Gen Z students at Jombang University. The studies strategy used in this studies is a survey-based quantitative technique. In order to gather data, 96 individuals were chosen using a purposive sample method and given a Likert-scale questionnaire. With the help of the SmartPLS 4.0 tool, the studies data was analyzed utilizing PLS-SEM technique. The results demonstrate that religious beliefs and Islamic economic literacy positively affect the propensity to engage in online business. The impact of Islamic economic literacy and religious beliefs on transaction intentions was shown to be mediated by Muslim consumer attitudes. Also, e-commerce purchase intent is positively impacted by Muslim customer views. Students' favorable views and intents to transact via e-commerce platforms that conform with Sharia rules may be strengthened by strengthening their Islamic economic literacy and religiosity, according to this research. Universities, e-commerce operators, and other relevant organizations should prioritize Islamic economic literacy instruction and work to develop religious values in order to promote digital transaction behavior that is in line with Sharia standards, according to the implications of this study